Use of vaccine and probiotic in the control of swine diarrhea caused by enterotoxigenic Escherichia coli - Avila, F. A.; Schocken-Iturrino, R. P.; Quintana, J. L.; Basso, A.; Ambrosim, J. A. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1998)
A total of 42 pregnant sows were divided into eight groups and submitted to the following treatments: group I with seven unvaccinated sows whose piglets did not receive probiotic, was used as control, group II with five vaccinated sows whose piglets did not receive probiotic, groups III, IV and V with five vaccinated sows each whose piglets received probiotic for 5, 15 and 28 days, respectively, and groups VI, VII and VIII with five unvaccinated sows each whose piglets received probiotic for 5, 15 and 28 days, respectively. Each animal in the vaccinated groups received subcutaneously Two doses of 5.0ml of vaccine containing pill K88, K99, 987P and F42 of Escherichia coli. The probiotic contained Lactobacillus acidophilus at the dose of 2.0x10(8) live cells in 20ml of milk and was administered orally. All animals were observed clinically and bacteriologically and the titers of anti-K88, anti-K99, anti-987P and anti-F42 antibodies were determined in serum and colostrum. The results showed that the vaccine associated to the probiotic administered for 28 days was the most effective treatment for the control of diarrhea caused by enterotoxigenic Escherichia coli.
Keywords: swine; Escherichia coli; Lactobacillus acidophilus; vaccine; probiotic